2011
DOI: 10.1111/j.1365-2702.2011.03882.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual problems in women during the first postpartum year and related conditions

Abstract: Healthcare professionals should evaluate women in terms of their sexual functions during both pregnancy and postpartum period. Health education, counselling, referral services for early diagnosis and treatment might contribute to the protection and improvement of the sexual health of women during the postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
2
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 31 publications
(44 reference statements)
7
72
2
14
Order By: Relevance
“…Caring for women integrally means being concerned with their sexual health, requiring nurses to search for theoretical and practical approaches on the strategies that enable confrontation of this reality. (1,3,4,11) Similar results were identified in a study of women in the first 3 months of postpartum, in which it was identified that 83% of them experienced sexual problems, decreasing to 64% at 6 months -although not reaching pre-pregnancy levels of 38%. (12) In this sense, the fact is that health professionals need to be aware of issues related to sexuality of women/couples.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Caring for women integrally means being concerned with their sexual health, requiring nurses to search for theoretical and practical approaches on the strategies that enable confrontation of this reality. (1,3,4,11) Similar results were identified in a study of women in the first 3 months of postpartum, in which it was identified that 83% of them experienced sexual problems, decreasing to 64% at 6 months -although not reaching pre-pregnancy levels of 38%. (12) In this sense, the fact is that health professionals need to be aware of issues related to sexuality of women/couples.…”
Section: Discussionsupporting
confidence: 70%
“…Studies show that although many couples present sexual difficulties, especially after the first birth, few are those who, in fact, seek professional help. (1,3,4,14) Regarding types of sexual dysfunctions identified in this study, we recognized more frequently, dyspareunia, vaginismus, dysfunction of desire and orgasmic, and finally, dysfunction of arousal stage. The factors associated with these dysfunctions were women belonging to the Catholic or Protestant religion; working over 8 hours/daily; vaginal delivery with suture; the presence of dyspareunia during pregnancy; and the presence of vaginismus before pregnancy.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations